Melorheostotic Bone Lesions Caused by Somatic Mutations in MAP2K1 Have Deteriorated Microarchitecture and Periosteal Reaction. (22nd January 2019) - Fratzl‐Zelman, Nadja; Roschger, Paul; Kang, Heeseog; Jha, Smita; Roschger, Andreas; Blouin, Stéphane; Deng, Zuoming; Cabral, Wayne A; Ivovic, Aleksandra; Katz, James; Siegel, Richard M; Klaushofer, Klaus; et al.
ABSTRACT: Melorheostosis is a rare non‐hereditary condition characterized by dense hyperostotic lesions with radiographic "dripping candle wax" appearance. Somatic activating mutations in MAP2K1 have recently been identified as a cause of melorheostosis. However, little is known about the development, composition, structure, and mechanical properties of the bone lesions. We performed a multi‐method phenotype characterization of material properties in affected and unaffected bone biopsy samples from six melorheostosis patients with MAP2K1 mutations. On standard histology, lesions show a zone with intensively remodeled osteonal‐like structure and prominent osteoid accumulation, covered by a shell formed through bone apposition, consisting of compact multi‐layered lamellae oriented parallel to the periosteal surface and devoid of osteoid. Compared with unaffected bone, melorheostotic bone has lower average mineralization density measured by quantitative backscattered electron imaging (CaMean: –4.5%, p = 0.04). The lamellar portion of the lesion is even less mineralized, possibly because the newly deposited material has younger tissue age. Affected bone has higher porosity by micro‐CT, due to increased tissue vascularity and elevated 2D‐microporosity (osteocyte lacunar porosity: +39%, p = 0.01) determined on quantitative backscattered electron images. Furthermore, nano‐indentation modulus characterizing material hardness and stiffness was strictly dependent on tissue mineralization (correlation with typical calcium concentration, CaPeak: r = 0.8984, p = 0.0150, and r = 0.9788, p = 0.0007, respectively) in both affected and unaffected bone, indicating that the surgical hardness of melorheostotic lesions results from their lamellar structure. The results suggest a model for pathophysiology of melorheostosis caused by somatic activating mutations in MAP2K1, in which the genetically induced gradual deterioration of bone microarchitecture triggers a periosteal reaction, similar to the process found to occur after bone infection or local trauma, and leads to an overall cortical outgrowth. The micromechanical properties of the lesions reflect their structural heterogeneity and correlate with local variations in mineral content, tissue age, and remodeling rates, in the same way as normal bone. © 2018 American Society for Bone and Mineral Research Abstract : Development of the melorheostotic lesion.